PERANCANGAN APARTEMEN SOHO DI SLIPI JAKARTA BARAT DENGAN PENDEKATAN ARSITEKTUR HYBRID - Saefudin, Slamet (Universitas Mercu Buana, 2024)
HYB SOHO, the Small Office Home Office concept is an integration between residential and office, which provides 2 floors in each unit, with a height of 7 meters from floor to floor, balconies in each unit, and other supporting facilities such as Gym, Jogging Track, and Swimming Pool. This concept produces a residence that offers a comfortable apartment as well as a home office. HYB = HYBRID The building concept in this design is a hybrid architecture that combines Jakarta's heritage architecture, buildings that have important cultural, historical, and social values, with modern architecture to create something new. Slipi, West Jakarta, is a strategic area with good accessibility. The location is close to the business center and offices in Central Jakarta and has easy access to various public facilities such as shopping centers, restaurants and public transportation. The SoHo (Small Office Home Office) Apartment in the Slipi area can be an attractive choice because of its large market potential.